Antimicrobial resistance in South East Asia: Time to ask the right questions - Kakkar, M.; Chatterjee, P.; Chauhan, A.S.; Grace, Delia; Lindahl, Johanna F.; Beeche, A.; Jing, F.; Chotinan, S. (Informa UK Limited, 2018)
Antimicrobial resistance (AMR) has emerged as a major public health concern, around which the international leadership has come together to form strategic partnerships and action plans. The main driving force behind the emergence of AMR is selection pressure created due to consumption of antibiotics. Consumption of antibiotics in human as well as animal sectors are driven by a complex interplay of determinants, many of which are typical to the local settings. Several sensitive and essential realities are tied with antibiotic consumption – food security, livelihoods, poverty alleviation, healthcare access and national economies, to name a few. That makes one-size-fits-all policies, framed with the developed country context in mind, inappropriate for developing countries. Many countries in the South East Asian Region have some policy structures in place to deal with AMR, but most of them lack detailed implementation plans or monitoring structures. In this current debates piece, the authors argue that the principles driving the AMR agenda in the South East Asian countries need to be dealt with using locally relevant policy structures. Strategies, which have successfully reduced the burden of AMR in the developed countries, should be evaluated in the developing country contexts instead of ad hoc implementation. The Global Action Plan on AMR encourages member states to develop locally relevant National Action Plans on AMR. This policy position should be leveraged to develop and deploy locally relevant strategies, which are based on a situation analysis of the local systems, and are likely to meet the needs of the individual member states.